A tale of two universities: a comparison of college students' attitudes about concealed carry on campus. Issue 2 (April 2018) - Schildkraut, Jaclyn; Jennings, Kevin; Carr, Collin; Terranova, Victoria
Abstract In the aftermath of the 2007 Virginia Tech shootings, policymakers have sought ways to improve safety on college and university campuses nationwide, such as proposing to permit concealed carry license holders to carry on campus. To date, nine states—with Texas being the most recent—have enacted legislation implementing this measure. A limited body of research examines perceptions of students and other members of the campus community about these laws and their passage, with a focus on demographic variations in such attitudes. The present study extends this by considering the potential variation in attitudes by location. The results indicate that both region and gun ownership strongly predict attitudes favorable of such laws, but do so independent of one another. Additional findings, as well as limitations of the study, also are discussed.